Quality of Biofeedback in the Loop of Paced Breathing and Heart Rate Variability Parameters in Healthy Volunteers with Psychasthenic Personality Type in Repeated Series of Sessions - RubanА.; VynokurovaА.; Belal, S.; Martynenko, O.; Yabluchanskiy, N. (Psychiatry, Neurology and Medical Psychology)
On 15 healthy volunteers with psychasthenic personality type aged from 18 to 27 years (10 women and 5 men) the quality ofbiofeedback repeated series in the loop of paced breathing with the start from free breathing under the control of heart rate variability parameters was examined. It was found that volunteers with psychasthenic personality type showed low efficiency of the first biofeedback series in the proposed loop, however, holding of repeated series allows to achieve optimal state of regulatory systems. The high efficiency of repeated biofeedback sessions in the loop of paced breathing under the control of heart rate variability parameters in patients with psychasthenic personality type allows to recommend this technique for wide use in clinical and preventive medicine.